Indications and Challenges of Limb Amputation in Children; Experience in a Tertiary Hospital in Enugu Nigeria - Okenwa, Wilfred Okwudili (Nigerian Journal of Orthopaedics and Trauma, 2020)
Background: Limb amputations in children are generally an uncommon procedure and are usually associated with significant emotional implications for the patients and their caregivers. Apart from emotional issues, this surgical procedure, which is often life‑saving is fraught with challenges in a developing country. The aim of the study was to review indications and challenges posed by presentation and consent time in managing children who need amputation. It is hoped that highlighting the challenges will be helpful in improving care for children who may be involved. Patients and Methods: This was a retrospective study of all children 16 years and below who had limb amputation in Enugu State University of Technology Teaching hospital between January 2015 and December 2019. Results: They were 22 amputations involving 13 (59.0%) males and 9 (41.0%) females, giving a ratio of 1.4:1. Amputations of the lower limb occurred in 15 (68.2%) cases, while the upper limb was involved in 7 (31.8%) cases. Road traffic accident (RTA) 6 (27.3%) and sequalae of Traditional bone setter’s (TBS) intervention 6 (27.3%) after trauma were the most common indications for amputation. Delayed wound healing was the most common complication seen. No mortality was recorded, and consent for surgery was the most common challenge encountered. None of the patients was able to acquire prosthesis due to financial constraints. Conclusion: RTA and bone setter’s intervention in trauma management leading to gangrene are the most common indications for amputation in children. Comprehensive Child health care plan addressing observed challenges could bring a better outcome in children who may need amputation.